Evaluasi Rencana Pengembangan Kolam Labuh Pelabuhan Pt Semen Gresik Di Tuban - Perpustakaan UGM, i-lib ([Yogyakarta] : Fak. Biologi UGM, 2000)
Dredging-works for harbour basin maintenance is relatively costly. In order to reduce the dredging-works activities, evaluation on the design of the harbour basin for PT Semen Gresik Industry should be carried out carefully. Based on the wave data surrounding Tuban area, the location of the surf-zone and breaking zone can he distinguished and plotted in the bathymetric chart. Using this chart, it can be shown that the location of the harbour basin in the area of surf zone, and this mean that the harbour basin will be terribly silted. To reduce this siltation it is recommended to build under water sill surrounding the harbour basin or to relocate the jetty to the depth of -13,0 m.